Temporal stability of optimism and pessimism (LOT-R) over 6 years in the general population - Hinz, Andreas; Friedrich, Michael; Glaesmer, Heide; Brendel, Barbara; Nesterko, Yuriy; Ernst, Jochen; Schroeter, Matthias L.; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2024)
The aims of this study were to examine changes in habitual optimism over a six-year period and to analyze the relationship between changes in optimism and changes in other quality of life-related variables.Method: A randomly selected community sample of the German adult general population (N = 4965) was surveyed twice, with a time interval of 6.04 years.During the course of the six years, the mean score of the LOT-R total scale improved (effect size d = 0.11). The temporal stability in terms of the test-retest correlation was r = .61 for the total sample. There were only marginal gender differences in this temporal stability, however, the stability in the oldest age group ≥ 70 years (r = .50) was lower than the stability of the other age groups. The cross-sectional correlations showed clear relationships between optimism on the one hand and quality of life, life satisfaction, social support, and low levels of anxiety and physical complaints on the other. The corresponding longitudinal correlations between changes in optimism and changes in the other variables were less pronounced, but in the same direction.The study confirmed the applicability of the LOT-R in longitudinal studies. In samples with participants of 70 years and above, the limited stability in the optimism assessments needs to be considered in clinical practice and epidemiologic research.